Day case total laparoscopic hysterectomy in a low resource setting: A descriptive analysis - Vishal Bahall; Keevan Singh; Lance De Barry (Women's Health)
Background: A laparoscopic approach to hysterectomy can significantly reduce patient morbidity and improve the quality of recovery. Subsequent perioperative advances have led to an increasingly shorter hospitalization period following laparoscopic surgery, with the same-day discharge being common. However, due to infrastructural challenges, these shorter times to discharge have mostly been limited to developed countries. Objectives: To provide a descriptive analysis and evaluate the safety and feasibility of day-case laparoscopic hysterectomy in Trinidad and Tobago. Design: A retrospective analysis of all total laparoscopic hysterectomies over a 3-year period at a secondary medical center in Trinidad and Tobago. Methods: The medical records of 154 women who underwent total laparoscopic hysterectomy (TLH) from January 2020 to January 2023 were reviewed. Patient demographics, indications for surgery, perioperative variables, requirements for any additional operative procedures, and perioperative complications were recorded and analyzed. The perioperative management protocol was also outlined. Results: The most common indication for TLH was uterine leiomyoma (45%), followed by endometrial cancer (17.5%). In this study, 96% of patients were discharged satisfactorily within 24 h of surgery, and the mean ± standard deviation (SD) duration of hospitalization was 21 ± 2 h. The mean ± SD surgical time was 91 ± 36 min, and the average estimated blood loss was 93 ± 31 ml. No patients required postoperative blood transfusion. No postoperative opioids were required in 41% of patients, and no perioperative mortality was recorded in this study, with no patients requiring re-operation. Four postoperative complications were noted (2.6%), and this included two patients who developed deep vein thrombosis (DVT) (1.3%), one port-site infection (0.6%), and one case of pulmonary embolism (0.6%). The 30-day readmission rate was 1.9%, and this comprised the patients with DVT and pulmonary embolism. On subgroup analysis, there was no difference in surgical time between patients with body mass index >30 kg/m 2 , uterine size >12 weeks, and previous abdominal surgery ( p  > 0.05). Conclusion: Day-case laparoscopic hysterectomy is feasible in a low-resource setting like Trinidad and Tobago. The procedure is safe and associated with a low postoperative complication rate.